Glomerulonephritis associated with tuberculosis: A case report and literature review. Issue 6 (16th January 2013) - Solak, Yalcin; Gaipov, Abduzhappar; Anil, Melih; Atalay, Huseyin; Ozbek, Orhan; Turkmen, Kultigin; Polat, Ilker; Turk, Suleyman
Abstract: Rapidly progressive glomerulonephritis caused mycobacterium tuberculosis is rare; however, three case have been reported to date. Crescentic glomerulonephritis is a life‐threatening disease and together with the presence of tuberculous infection is associated with a poor outcome if treatment is inadequate and delayed. We describe the case of a 31‐year‐old female patient with nephrotic syndrome and progressive renal failure secondary to pulmonary tuberculosis. Renal biopsy showed crescent formation in 14 out of 27 glomeruli, and there was diffuse linear staining of immunoglobulin G deposits. Treatment included corticosteroids in combination with antituberculosis drugs for 2 months, and resulted in a significant improvement in renal function, the disappearance of proteinuria and pulmonary symptoms. We also present a review of the pertinent literature and discuss the pathophysiology of tuberculosis‐related acute postinfectious glomerulonephritis.